The Effect Of Flashcard On Students’ Motivation In Speaking Skill At Sman 10 Mataram - Imansyah Imansyah; Terasne Terasne (Mandala, 2019)
This research was aimed at finding out the effecton students’ motivation in speaking skill at SMAN 10 Mataram in academic year 2018/2019. The research was experimental with quasi experimental design. The population of the study was the tenth grade students of SMAN 10 Mataram that consisted of five classes. Two classes were chosen as the samples, those were X MIPA 1 as experimental group and X MIPA 2 as control group. They were chosen by using cluster random sampling. Experimental group treated by using flashcard and control group treated by using word wall. The data of the research were gathered from questionnaire test and the data analysis used inferential analysis. Based on the data analysis was gotten t-test = 3.801 and t-table = 1.684. It means that t-test was higher than t-table (3.801 > 1.684) with signification level 0.05. So that way, alternative hypothesis (Ha) accepted and null hypothesis (Ho) rejected. Therefore, it took conclusion that there is effect of flashcard on students' motivation in speaking skill at SMAN 10 Mataram in academic year 2018/2019.